Efektivitas Biofumigan Sawi Pahit Terhadap Nematoda Puru Akar (Meloidogyne spp.) Pada Tanaman Seledri (Apium graveolens L.) - Isna Rahma Yani Yani; Dewi Fitriyanti Fitriyanti; Lyswiana Aphrodyanti Aphrodyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Celery plants (Apium graveolens L.) have export value and are included in the important leaf vegetable group. Disturbances caused by plant-disturbing organisms in celery cultivation are still a problem that is always faced by farmers. The pest that is often found infecting celery plants, especially in the Landasan Ulin Utara area, Liang Anggang District, Banjarbaru City, South Kalimantan Province, is the Root Knot Nematode (NPA) (Meloidogyne spp). The symptoms of this NPA attack are very typical, namely the roots become swollen because nematode attacks the root system and disrupts the root tissue. Therefore, before causing greater losses, it needs to be anticipated. Control can be carried out by means of biofumigation, namely using bitter mustard greens waste which comes from the Brassicae family because it contains glucosinolates (GSL) and isothiocyanate compounds (ITS). This research aims to determine whether biofumigants from chopped bitter mustard greens are effective in controlling Meloidogyne spp. on celery plants. This research used a one-factor Completely Randomized Design (CRD) method, namely treatment with 500 Meloidogyne spp eggs. (control/T0) and 4 treatments with chopped bitter mustard greens, namely 500 Meloidogyne spp. + 200 grams of chopped bitter mustard greens (T1) 500 eggs of Meloidogyne spp. + 400 grams of chopped bitter mustard greens (T2) 500 eggs of Meloidogyne spp. + 600 grams of chopped bitter mustard greens (T3) and 500 Meloidogyne spp eggs. + 800 grams of chopped bitter mustard greens (T4). The results of this study show that celery plants treated with T4 can reduce disease severity and the average number of NPA populations. The highest disease severity was found in T0 plants with a percentage of 45.0% and the lowest percentage was in T4 treatment plants at 4.2%. The highest NPA population was also found in T0 plants, namely 428,125 individuals and the lowest population was in T4 plants, amounting to 126,125 individuals.